Environmental Determination and the Development of Trzciniec Cultural Circle Settlement in the Oder and Vistula River Catchments - Górski, Jacek; Makarowicz, Przemysław (Instytut Archeologii Uniwersytetu Rzeszowskiego, 2011)
An analysis of settlement in both upland and lowland zones reveals that the Bronze Age societies were quite capable of adapting to life in areas with different resource possibilities. The occurrence of a variety of settlement forms and occupation of diverse and radically different ecosystems, testify to the economic flexibility typical of Trzciniec Cultural Circle populations.
Keywords: Settlement patterns; Vistula; Subsistence; Trzciniec circle; Oder